Integrating MIMO and RoF technologies for low-latency and high-capacity 5G networks - Ullah, Rahat; Ali, Farman; Armghan, Ammar; Afsar, Haleem; Alshamrani, Ali; Roslee, Mardeni (Frontiers in Physics, 2025)
The exponential growth of Internet of Things (IoT) applications places unprecedented demands on current 5G communication networks. Existing 5G systems often lack advanced multiple input multiple output (MIMO) transmission capabilities and fall short in delivering high data rates, wide bandwidth, and ultra-low latency. To overcome these limitations, integrating emerging optical and wireless technologies is essential. This study proposes a hybrid communication framework that integrates wavelength division multiplexing (WDM)-based MIMO with radio over fiber (RoF) technology. Additionally, offset quadrature amplitude modulation (OQAM)-based multicarrier signals are employed to enhance the robustness of the MIMO transmission. The system performance is evaluated using data signals of 119 Gbps and 132 Gbps across a 3×3 MIMO configuration with antennas of varying polarization characteristics. Quantitative simulations confirm the proposed system’s capability to support high-capacity data transmission while maintaining low latency. The integrated WDM-MIMO-RoF framework demonstrates strong scalability and improved spectral efficiency compared to conventional 5G architectures. The findings validate the potential of combining WDM, MIMO, and RoF technologies to address the limitations of current 5G systems. This integrated approach paves the way for next-generation communication networks, offering promising directions for future research and deployment in high-demand IoT environments.